How Do Doctoral Students Experience Writing and Thesis production? Qualitative Analysis of the Irish National Survey of Postgraduate Students - Share, Michelle (FoodCloud, 2023)
Higher education (HE) policy emphasises the importance of high-quality doctoral education that prepares graduates for the knowledge economy. To support this, HE policy fora and higher education institutions (HEIs) have focused on institutional training programmes for doctoral supervisors. Writing and thesis production are central to the experience and success of doctoral students yet, in an Irish context, this topic has received little research attention. We applied the research question ‘how do doctoral students in Irish HEIs experience writing and thesis production’ to the free-text responses in the 2019 PGR StudentSurvey.ie dataset. Qualitative thematic analysis identified three main themes in doctoral students’ comments: a zone of uncertainty, writing and the role of the supervisor and institutional responsibilities. The paper highlights that doctoral students have unmet writing support needs. It also identifies the importance of institutional supports, such as physical writing space, and calls for a reimagination of current doctoral supervision and academic writing practice to enable discursive spaces of collaboration for students, their supervisors and discipline specific writing specialists.
PUBLISHED
Keywords: Doctoral students; Doctoral supervision; Doctoral writing; PhD students; Higher Education; doctoral education